PENDAMPINGAN PENGEMBANGAN SISTEM PERTANIAN ORGANIK BERKELANJUTAN DI THE LEARNING FARM - Paranita Asnur; Aisyah Aisyah; Veronika Widi Prabawasari; Dimyati Dimyati; X Furuhito; Bima Haryadi; Azaz Pradana; Budi Santosa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
The mentoring activity for developing a sustainable organic farming system at The Learning Farm (TLF) aims to document potential, identify constraints, and provide strategic recommendations to strengthen organic farming practices. The program was carried out through field surveys, direct observations, interviews, and questionnaires administered to partner farmers to gather information on cultivation practices, knowledge, and their needs. The collected data were analyzed qualitatively and descriptively as the basis for formulating mentoring strategies. Survey results show that each vegetable commodity produces an average of 10–15 kg per harvest, with some reaching up to 40 kg, harvested twice a week or approximately 97 times a year. TLF has implemented organic farming through crop rotation, multiple cropping, and intercropping with perennial plants such as robusta coffee. Fertilization is carried out using solid and liquid organic fertilizers produced independently, while irrigation utilizes river water filtered with water hyacinth. The main challenges include limited capital, nutrient-poor soil conditions, high rainfall, and high labor requirements. Nevertheless, the organic farming sector contributes more than 50% of TLF’s income, surpassing the agritourism sector. The implications of this activity emphasize that organic farming is not only environmentally friendly but also economically significant. Multidisciplinary mentoring is required to strengthen farmers’ capacity, optimize cultivation systems, and support TLF as a center for education and innovation in sustainable agriculture